Biochar como enmienda orgánica del suelo en los cultivos hortícolas - Arechua Contreras, Pedro Adrián (2024)
In the development of this research based on "Biochar as an organic soil amendment in horticultural crops." in which it was proposed as an objective to describe Biochar as an organic soil amendment to improve the productivity of horticultural crops. The methodology is determined to be based on a basic type of research, where it was developed under a descriptive-analytical approach, with a qualitative research design, in its development to determine the horticultural crops in Ecuador, the quality of horticultural products in Ecuador, the main horticultural crops in Ecuador, their Sustainability and Technological Innovation, their application in soils, the benefits and applications of in Agriculture, the use and application of Biochar, the environmental impact of biochar, the reduction of greenhouse gases, and carbon sequestration. Regarding the results, biochar improves soil fertility and reduces the need for fertilizers; Its porous structure improves soil aeration and drainage, which favors the growth of beneficial microorganisms, to maximize benefits and minimize negative effects, you should start with low doses; recommends a dose of 2-4 liters per square 100 meter, mixed 50% with compost, worm castings or manure, to produce 39.5 tons of tomatoes per hectare. In conclusion, it was shown that biochar reduces soil pollution and greenhouse gases by adsorbing pollutants and sequestering carbon over a long period of time, through the pyrolysis of agricultural, forestry waste or manure, it is a carbon material resistant to oxidation that can last hundreds or thousands of years.